RANCANG BANGUN SISTEM INFORMASI BERBASIS WEB MANAJEMEN PERPUSTAKAAN UNIVERSITAS TABANAN - Ni Made Dwi Laksmi; IGKG Puritan Wijaya ADH; Dian Rahmani Putri (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
Library management information system is the application of information systems in the library to support the information needed by all levels of library management.  In this study, the purpose of creating an information system is to help the library overcome data management and speed up the service process for the better. The research method used in making this information system starts by conducting effectiveness testing which is then continued with the collection of data needed by conducting interviews and observations. In making the system, the concept of planning and design through the stages of data collection, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), database and then implement it. The software used in the design and implementation is Laragon as a webserver, MYSQL as a database, and Visual Studio Code as an editor using PHP and HTML writing. The results of this study prove that the Management Information System implemented into the library system makes the system able to provide convenience in managing data and the library service process becomes faster.